Analysis of Production Technology of Wood Briquettes, Including Costs and Distribution (Agricultural Engineering, 2020)
The paper analyzes the costs of production of wood sawdust briquettes, manufactured by the company Brykiet-Pol2, based in Goleszów in southern Poland. In addition, production technology, raw material supply and distribution of the finished product were analyzed. The costs of producing one ton of briquettes for the four assessed variants ranged from PLN 364.8 (option D) to PLN 648.7 (option A). The cost structure was dominated by the purchase of raw material and depreciation of the technological line. The most economically advantageous production variant was option C, currently implemented in the company (production costs: PLN 458.7·t−1), and the proposed option D, using two briquetting presses. The latter option increased production efficiency and reduced unit costs of briquette production in a three-shift system around the clock.